Two Year Outcome After Chronic Iliac Vein Occlusion Recanalisation Using the Vici Venous Stent®. (November 2018) - Black, Stephen; Gwozdz, Adam; Karunanithy, Narayan; Silickas, Justinas; Breen, Karen; Hunt, Beverley; Smith, Alberto; Cohen, Ander; Saha, Prakash
Abstract : Objective/background: The aim was to assess two year outcomes with placement of the Vici Venous Stent ® in patients with chronic iliofemoral venous occlusions (complete blockage). Methods: This was a retrospective single centre study comprising patients treated with the Vici Venous Stent for venographically verified iliofemoral venous occlusion and post-thrombotic syndrome (Villalta score ≥ 5 points) at least 12 months after acute deep vein thrombosis. Venography and intravascular ultrasound were used peri-operatively; duplex ultrasound was used to assess stent patency during follow up. Results: Eighty-eight patients (101 limbs) had stent placement between March 2014 and October 2016. Median pre-treatment Villalta score was 14 (range 5–33). Stenting extended across the inguinal ligament in 63 limbs (62%) in order to land in a healthy venous segment. Six patients (7%) required endophlebectomy and fistula creation. Median imaging follow up was 21 months (range 0–41 months). Primary, assisted primary and secondary patency rates at one year were 59%, 78%, and 87%, respectively, and two years 51%, 73%, and 82%, respectively. Forty-three limbs (43%) had re-intervention (lysis, venoplasty, and/or placement of stent) during follow up; median time to re-intervention was 32 days (range 0–520 days). At 24 months, 37 of 53 limbs (70%) with available Villalta assessment showed clinically significant improvement (>30% reduction of baseline score). Villalta scores at the 6, 12, and 24 month clinical follow up were significantly lower than before stenting ( p  < .001, all time points). In a subset analyses of limbs with stenting terminating above and below the inguinal ligament, secondary cumulative patency rates at 24 months were 90% and 79%, respectively; clinical outcome showed 58% vs. 73% of limbs with clinically significant improvement, respectively. There was no statistically significant difference in patency or clinical outcomes. Conclusion: The Vici Venous Stent is associated with a good secondary patency rate and durable and substantial symptomatic resolution in patients with chronic post-thrombotic occlusions, regardless of whether stents extended beneath the inguinal ligament.